East Africa : Lord Lugard's scheme (embracing Kenya and Uganda only) - Lugard, Frederick John Dealtry 1858-1945; Großbritannien. Colonial Office; National Archives (Großbritannien); Adam Matthew Digital (Adam Matthew Digital, 1931)
Colonial Office file containing correspondence and memoranda concerning Lord Lugard's proposal for closer union between Kenya and Uganda under a single governor or high commissioner